Evaluation of persimmon cultivars in Campania (Italy) - Insero O.; De Luca A.; Rega P. (First Mediterranean symposium on persimmon, 2002)
Kaki Tipo', a Pollination Variant Non Astringent (PVNA) cultivar, represents over 90 per cent of Campania's production. Only a modest quantity of the local cultivars ('Zellona', 'Melella', 'Cioccolatino', 'Lampadina', etc.) are employed as pollinators. The fruits of these cultivars are generally small, early ripening, with vanilla-coloured flesh, high sugar concentration, six to eight seeds per fruit, and are ready for consumption at harvest. They are much appreciated by local consumers. Since the 1970's, the Caserta Section of the Experimental Institute for Fruit Crops has worked for the introduction of new cultivars of Italian and foreign origin to evaluate their productive behaviour in Campania. The following recently introduced cultivars have been tested at the Experimental Station 'Aia Spaccata', Francolise (Caserta): Pollination Constant Astringent (PCA) Group - 'Yamato', 'Saijo'; Pollination Constant Non Astringent (PCNA) Group - 'Hana Gosho', 'Yamato Gosho', 'Maekawa Jiro', 'Matsumoto Wase Fuyu', 'Koda Gosho', 'Izu' and 'Suruga'; PVNA Group 'Mikatani Gosho'; Pollination Variant Astringent (PVA) - 'Hiratanenashi'.
1. Mediterranean Symposium on Persimmon, 2001/11/23-24, Faenza (Italy)